PPAR Regulation of Inflammatory Signaling in CNS Diseases - John J. Bright; Saravanan Kanakasabai; Wanida Chearwae; Sharmistha Chakraborty (PPAR Research)
Central nervous system (CNS) is an immune privileged site, nevertheless inflammation associates with many CNS diseases. Peroxisome proliferator-activated receptors (PPARs) are a family of nuclear hormone receptors that regulate immune and inflammatory responses. Specific ligands for PPAR𝛼, 𝛾, and 𝛿 isoforms have proven effective in the animal models of multiple sclerosis (MS), Alzheimer's disease, Parkinson's disease, and trauma/stroke, suggesting their use in the treatment of neuroinflammatory diseases. The activation of NF-𝜅B and Jak-Stat signaling pathways and secretion of inflammatory cytokines are critical in the pathogenesis of CNS diseases. Interestingly, PPAR agonists mitigate CNS disease by modulating inflammatory signaling network in immune cells. In this manuscript, we review the current knowledge on how PPARs regulate neuroinflammatory signaling networks in CNS diseases.